Ethnobotanical investigation of medicinal plants in Buska Mountain range, Hamar district, Southwestern Ethiopia - Melese Bekele; Feleke Woldeyes; Ermias Lulekal; Tamrat Bekele; Sebsebe Demissew (BMC, 2022)
Abstract Background Despite the fact that ethnobotanical studies have been conducted in various parts of Ethiopia, compared with the existence of the multitude and diverse ethnic groups and their associated traditional knowledge, the studies are not comprehensive enough for all the localities and communities in the country. This is also true for the Hamar community of Southwestern Ethiopia, who are totally dependent on plants and plant products for their livelihood. Hence, this investigation was done to identify and record medicine plants and the native wisdom of the community in the area. Methods Three hundred twenty six (326) informants were selected from the 12 lowest governmental units (Kebeles) applying Cochran's formula through stratified random sampling technique. From the total informants, 74 (48 males and 26 females) were purposively selected for in-depth discussion. Semi-structured interviews, focus group discussions, guided field walks as well as market surveys were used for data collection. Standard ethnobotanical analytical tools comprising ranking and comparison were used for the analysis. Preference ranking, pair-wise comparison, informant consensus factor, direct matrix ranking, Cultural Significance Index (CSI) and Jaccard's similarity coefficient (JCS) as well as Analysis of Variances (ANOVA), applying SPSS (version 20) were computed. Results A total of 145 species practical to cure about 72 ailments of livestock and humans were recorded. Families Fabaceae (with 22% of species), Asteraceae (11%), and Lamiaceae (9%) were discovered as the most dominant families in the area. Shrubs contributed the most (40%) to the growth forms followed by herbs (26.5%). Fresh leaves of the plants were parts that are used most frequently in the area. The highest ICF value (0.94) was recorded for reproductive problem categories. There was a relatively very high dependence of the community on plants and plant products together with a hoarded indigenous knowledge in the area that positively correlated with age (r = 0.82). Conclusion The study's findings revealed that Buska Mountain range is a home for highly diverse and most dependable plant species and associated indigenous knowledge. However, because of the realized environmental threats in the area, the conservation efforts of the community should be invigorated and supported in order to sustain the biodiversity in general and the medicinal plant species in particular.